Some Wood Properties of 10-Year-Old Eucalyptus Camaldulensis Dehnh. In Three Diametric Classes - Lima, Bianca M.; Amorim, Erick P.; Yamaji, Fábio M.; Freitas, Miguel L.M.; Barbosa, Juraci A.; Cambuim, José [UNESP]; Zaruma, Darlin U.G. [UNESP]; de Moraes, Mario L.T. [UNESP]; Longui, Eduardo L. (Sociedade Brasileira de Quimica (SBQ), 2022)
Multipurpose forests are becoming more frequent, but research on wood is still needed to target it for adequate industrial consumption. However, such determination requires a knowledge of the seed provenance and planting characteristics. Accordingly, this work aimed to characterize the wood quality of 10-year-old E. camaldulensis in three diametric classes for potential use in paper and cellulose production, energy and sawn wood. We studied 10 trees of each diameter class (small, middle, and large) and employed the usual techniques for analyses of each property. E. camaldulensis wood is characterized by an increased percentage of heartwood and a decreased percentage of sapwood as tree diameter increases. Basic density was higher in the larger class; however, this was not directly reflected in better results in other physical properties. For example, volumetric shrinkage was higher in the middle class. Anatomical features-imposed limitations on the presence of fines, and fiber dimensions-imposed limitations on the quality indexes for paper and cellulose, which are important for the industrial use of wood. Wood waste from Eucalyptus camaldulensis could be exploited for bioenergy since its HHV values range from 16425 to 17056 kJ.kg-1. In general, we suggest that trees in the studied spacing and edaphoclimatic conditions do have industrial utility, thus contributing to the forest-based market and reducing the exploitation of native species for this purpose. Based on its wood quality in different diameter classes, E. camaldulensis could benefit from the investment technological strategies to boost genetic gains and obtain better wood properties.
Keywords: Plant breeding; reforested wood; wood chemical properties; wood quality